"From factory to field": USAID and the logistics of foreign aid in Soviet-occupied Afghanistan. (August 2018) - Attewell, Wesley
Emerging critical scholarship on logistics has shown how the field is implicated in a broader necropolitics of violence, disposability, and exploitation. While much has been made of logistics' historical linkages to military and market forces, this paper, in contrast, explores how logisticians have played an increasingly central role in development and humanitarian missions to theatres of conflict and emergency. It focuses on the effort of the United States Agency for International Development (USAID) to supply mujahideen forces in Soviet-occupied Afghanistan with the non-lethal materiel necessary for their insurgency. It argues that USAID understood its relief and rehabilitation mission as a problem of logistics. By sketching the shifting contours of USAID's cross-border programming, this article offers a more nuanced diagnosis of how logistics has become essential to the management of life and death across multiple temporalities, spaces, and scales.